The 4th International Whale Shark Conference 2016
DOI: 10.5339/qproc.2016.iwsc4.26
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sex and size range of whale sharks and their sighting behaviour in relation to fishing lift nets in Borneo and Papua, Indonesia

Abstract: Background The composition of sex and size of a population is important for management and conservation of marine organisms, including high mobility and global species such as the whale shark, Rhincodon typus. The presence of fish in lift nets in some Indonesian waters attracts feeding whale sharks. The objective of our study was to compare the sex, size and behaviour of whale sharks associated with lift nets in Cenderawasih Bay, Papua and Talisayan, East Kalimantan. Approach Data sampling was conducted for 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Contrary to Maruanaya [ 40 ], who reported that whale sharks were only present in Pangandaran in the months of August and September, the records suggest their year-round presence. The whale sharks that were landed in Pangandaran Bay were between 3.5 and 15 m in length, averaging 6.9 m, and the larger sample averaged 6.7 m. This is markedly larger than the mean of 4.3 ± 1.0 m (range 3–7 m) of live whale sharks in Indonesian waters, as reported by Himawan et al [ 41 ]. Hsu et al [ 19 ] estimated that male whale sharks in the Indo-Pacific Oceans begin maturing at a total length of ~8.5 m and females at a total length of ~9.5 m. Colman [ 42 ] indicated that the whale sharks of both sexes at Ningaloo Reef, western Australia, mature at more than 9 m. This then suggests that all but four of the whale sharks landed on Java were not yet adults.…”
Section: Discussionmentioning
confidence: 56%
“…Contrary to Maruanaya [ 40 ], who reported that whale sharks were only present in Pangandaran in the months of August and September, the records suggest their year-round presence. The whale sharks that were landed in Pangandaran Bay were between 3.5 and 15 m in length, averaging 6.9 m, and the larger sample averaged 6.7 m. This is markedly larger than the mean of 4.3 ± 1.0 m (range 3–7 m) of live whale sharks in Indonesian waters, as reported by Himawan et al [ 41 ]. Hsu et al [ 19 ] estimated that male whale sharks in the Indo-Pacific Oceans begin maturing at a total length of ~8.5 m and females at a total length of ~9.5 m. Colman [ 42 ] indicated that the whale sharks of both sexes at Ningaloo Reef, western Australia, mature at more than 9 m. This then suggests that all but four of the whale sharks landed on Java were not yet adults.…”
Section: Discussionmentioning
confidence: 56%
“…Meanwhile, juvenile whale sharks tend to be found congregating in shallow waters near the coast (Dove and Pierce, 2021). In Indonesia, the whale shark is also found in Cenderawasih Bay, Papua (Manuhutu et al, 2021), Talisayan waters, Kalimantan (Himawan et al, 2017), and Probolinggo waters (Syah et al, 2018;Kapinangasih et al, 2022). Large adult whale sharks are rarely found on the coasts because of their diving abilities and adaptations that allow them to obtain more prey in deep waters (Dove and Pierce, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…An earlier study from January to December 2020 also reported the dominance of male whale sharks in this area [7]. Whale shark research studies at CBNP also reported male dominance although some females appeared from time to time [30].…”
Section: Sexmentioning
confidence: 87%